(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Development can be defined as improving the welfare of a society through appropriate social, political, and economic conditions including employment opportunities. This study is aimed at examining the impact of road development on rural employment (farming) in Etsako West local government area of Edo state through, taking inventory of rural employment in the study area, examining the existing road transport facilities in the area, assessing the effect of roads on rural employment and analyzing the impact of road transport on rural employment. Using both primary and secondary data for the study, the primary data were obtained through the use of questionnaires administered on 12 wards in the study area, administering 485 questionnaires in total and Scheduled interviews with the LGA secretariat. This was done using a systematic random sampling method. Findings revealed that farming accounts for 55.7% of employment, shifting cultivation is the most prominent type of agricultural practice, with represents 91.1%, Cassava, with 33. 3% is the predominant crop cultivated alongside Vegetables, Maize, Beans Groundnut and Yam, types of roads used to farms are mainly footpaths, earth roads and Tarred roads and majority of the farms are only connected with footpaths making accessibility to farm very poor and increasing the expected time spent to go to the farm and from the farm to the communities, this led to high cost of transport and abandonment of produce in farms, among others. The study therefore recommended Construction and Rehabilitation of Farm Access Roads, Adoption of Rural Road Network Planning, Provision of Maintenance Framework for Rural Roads, Subsidy and Transport Support for Farmers, Promotion of Larger and Commercial Farm Sizes and Integration of Agricultural and Road Development Policies